Lontara: Antara Religiusitas dan Kepercayaan - Patahillah Asba; Andi Andra Susastra; Khaerul Mannan (Jurnal Litigasi Amsir, 2022)
In general, the Bugis-Makassar people have known a belief before knowing Islam. Their belief is called attorioloang, and in some places, they call it attorioloang. In general, Bugis-Makassarese people have known a belief before knowing Islam. Their belief is called attorioloang, and in some places, they call it attorioloang. This research aims to find out the extent of the influence of Religion and Belief from Lontara's point of view. The results of the study show that the diversity and belief of the Bugis-Makassar people, which is identical to Islam, is still full of syncretism practices between Islamic and pre-Islamic teachings. This belief is sometimes associated with sacred places such as Mount Bawakaraeng in Gowa or Bulu' Iowa in Amparita (Sidrap). Some esoteric texts, which are highly sacred by their adherents, contain teachings that marry Islamic Sufism with the concept of divinity (theology) and the concept of the pre-Islamic Bugis-Makassar universe (cosmology).